Functional characterisation and cell specificity of BvSUT1, the transporter that loads sucrose into the phloem of sugar beet (Beta vulgaris L.) source leaves. (1st February 2017) - Nieberl, P.; Ehrl, C.; Pommerrenig, B.; Graus, D.; Marten, I.; Jung, B.; Ludewig, F.; Koch, W.; Harms, K.; Flügge, U.‐I.; Neuhaus, H. E.; Hedrich, R.; et al.
Abstract: Sugar beet ( Beta vulgaris L.) is one of the most important sugar‐producing plants worldwide and provides about one third of the sugar consumed by humans. Here we report on molecular characterisation of the BvSUT1 gene and on the functional characterisation of the encoded transporter. In contrast to the recently identified tonoplast‐localised sucrose transporter BvTST2.1 from sugar beet taproots, which evolved within the monosaccharide transporter (MST) superfamily, BvSUT1 represents a classical sucrose transporter and is a typical member of the disaccharide transporter (DST) superfamily. Transgenic Arabidopsis plants expressing the β ‐GLUCURONIDASE ( GUS ) reporter gene under control of the BvSUT1 ‐promoter showed GUS histochemical staining of their phloem; an anti‐BvSUT1‐antiserum identified the BvSUT1 transporter specifically in phloem companion cells. After expression of BvSUT1 cDNA in bakers' yeasts ( Saccharomyces cerevisiae ) uptake characteristics of the BvSUT1 protein were studied. Moreover, the sugar beet transporter was characterised as a proton‐coupled sucrose symporter in Xenopus laevis oocytes. Our findings indicate that BvSUT1 is the sucrose transporter that is responsible for loading of sucrose into the phloem of sugar beet source leaves delivering sucrose to the storage tissue in sugar beet taproot sinks.